2022
DOI: 10.1186/s12917-022-03253-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of lncRNAs and mRNAs by RNA-Seq in secondary hair follicle development and cycling (anagen, catagen and telogen) of Jiangnan cashmere goat (Capra hircus)

Abstract: Background Among the world’s finest natural fiber composites is derived from the secondary hair follicles (SHFs) of cashmere goats yield one of the world's best natural fibres. Their development and cycling are characterized by photoperiodism with diverse, well-orchestrated stimulatory and inhibitory signals. Long non-coding RNA (lncRNAs) and mRNAs play important roles in hair follicle (HF) development. However, not many studies have explored their specific functions in cashmere development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Most of these goats live in cold northern regions of China, and their cashmere has undergone intense artificial selection for protection from the cold and as a textile material. Cashmere is produced from the secondary hair follicle of cashmere goat [ 45 ], which is finer, softer and lighter, and it is considered a luxury textile fiber [ 46 ]. The morphological structure and development of secondary hair follicles directly affect the output and quality of cashmere.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these goats live in cold northern regions of China, and their cashmere has undergone intense artificial selection for protection from the cold and as a textile material. Cashmere is produced from the secondary hair follicle of cashmere goat [ 45 ], which is finer, softer and lighter, and it is considered a luxury textile fiber [ 46 ]. The morphological structure and development of secondary hair follicles directly affect the output and quality of cashmere.…”
Section: Discussionmentioning
confidence: 99%
“…Cashmere fiber is characterized by cyclical and seasonal growth, and does not grow during the period from the fall of the cashmere (late April and early May) to the regrowth of the body surface (late July and early August). Therefore, the growth cycle of cashmere fiber is divided into a non-growing period (from late spring to late summer) and a growing period (from early autumn to late winter) [2,3]. At present, it has been confirmed that nutrient levels during the cashmere growing period had a significant effect on cashmere production performance; however, the effect of nutrient levels during the cashmere nongrowing period on cashmere production performance remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cashmere fiber is characterized by cyclical and seasonal growth, which begins to appear and grow on the body surface in summer, continues to grow in autumn to early winter, stops growing in winter, and naturally sheds from the body surface in spring [1]. Therefore, the growth cycle of cashmere fiber is divided into a non-growing period (from late spring to late summer) and a growing period (from late summer to winter) [2,3]. Cashmere yield is determined by length, diameter, and number of cashmere fibers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…To study hair follicle cyclic growth and development, the majority of the researchers have used different developmental stages of the same population. For example, Wu et al selected three 2-year-old female Jiangnan Cashmere goats as experimental animals to screen the candidate lncRNAs, mRNAs, and related pathways affecting the three developmental stages of secondary hair follicles by RNA-seq ( 45 ). Similarly, Wang et al selected five 1-year-old female Capra hircus in their comprehensive analysis of genes encoding and non-coding RNAs of the hair follicle cycle, of which three were used to construct and analyze the lncRNA library and two for constructing miRNA library ( 46 ).…”
Section: Discussionmentioning
confidence: 99%